Preparation and characterization of nanoparticles containing an atypical antipsychotic agent - Singh S.; Muthu M.S. (My University, 2025)
Aim: The aim of this work was to prepare poly(ε-caprolactone) nanoparticles of risperidone and to characterize them. Methods: Risperidone-loaded poly(ε-caprolactone) nanoparticles were prepared by the nanoprecipitation method using poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock polymeric stabilizer (Pluronic® F-68). The particles were characterized for particle size by photon correlation spectroscopy and transmission electron microscopy. The free dissolved drug in the nanosuspension was determined by the bulk equilibrium reverse dialysis bag technique. In vitro release studies were carried out using the dialysis bag diffusion technique. Results: The particle size of the prepared nanoparticles ranged from 90 to 300 nm. Nanoparticles of risperidone were obtained with high encapsulation efficiency (70-80%). The drug release from the risperidone nanoparticles was sustained in some batches for more than 24 h with 80% drug release, whereas release from risperidone in polyethylene glycol 400 solution showed release within 2 h. Conclusion: These studies suggest the feasibility of formulating risperidone-loaded poly(ε-caprolactone) nanoparticles for the treatment of psychotic disorders. © 2007 Future Medicine Ltd.